Juridical Analysis Of The Pre-Trial Decision On The Criminal Act Of Assault (Case Study of Decision Number 06/Pid.Prap/2016/PN.Kpg.) - Pebrian, Mahesa Tezar; Mustika, Desty Anggie; Ferrary, Ande Aditya Iman (JURNAL MAHASISWA YUSTISI, 2025)
This study analyzes pre-trial proceedings as a vital instrument in the Indonesian criminal justice system, especially after its scope was expanded by the Constitutional Court. The examination of Decision Number 06/Pid.Prap/2016/PN.Kpg. is relevant for understanding how pre-trial judges apply limitations on their authority in reviewing the legality of investigation processes related to criminal acts of battery and maintaining a balance between law enforcement and the protection of individual rights. This research employs a normative juridical method, focusing on document study. Data was collected through the review of primary legal materials, such as the Criminal Procedure Code (KUHAP) and the subject decision, as well as secondary legal materials including legal theories, doctrines, and relevant literature. Data analysis was conducted qualitatively, interpreting and drawing conclusions on the legal implications of the decision, and identifying the consistency of the ruling with prevailing legal principles. The research findings indicate that the pre-trial judge in Decision Number 06/Pid.Prap/2016/PN.Kpg. consistently upheld the limits of pre-trial authority. The judge rejected the petition that sought to challenge the substantive merits of the battery case, focusing instead on the formal aspects and the sufficiency of preliminary evidence in the suspect’s designation. This rejection affirms that pre-trial proceedings are not a forum for adjudicating the substance of a case, but rather an essential procedural control mechanism to ensure legal certainty and protect individual human rights throughout every stage of the criminal process.